How to Become a Good Healer in Chinese Medicine? - Udo Lorenzen (Wolters Kluwer Health/LWW, 2020)
Today, traditional Chinese medicine (TCM) is a relatively new product of the People's Republic of China. About 1950 Chairman Mao aimed atthe standardization and simplification of many traditional medical schools to guarantee a stable health care for the population. As academic exchange between east and west increased during the last 60 years, TCM appears today more and more as the "real" and "old" Chinese medicine. But is that really the case? There is a famous saying in China: Medicine is also idea (医者意也Yi Zhe Yi Ye), so what are the ideas about a good healer? In my article I try to find it out. Searching through the old classical books, there are some good ideas about a good healer, especially in the Ling Shu (《灵枢》Spiritual Pivot). The root of all is the spirit (神Shen). There are many other requirements to be a good healer, but without a stable Shen, no treatment can really touches the cause of the disease!